Optimization of growth of two microalgal isolates for biofuel feedstock - Ali, NM; Tarin, NJ; Mondol, MN; Chamon, AS; Aziz, A; Rahman, MM (Bangladesh Journal of Scientific and Industrial Research, 2016)
A research involving random isolation and characterization of naturally occurring microalgae in Bangladesh was carried out for assessing their potential for biofuel feedstock and other uses. Among the isolates, one identified as a green alga Chlamydomonas noctigama and another one as blue-green alga Nostoc spongiaeforme were grown in modified Chu-10D medium. The optimization of their growth was performed following incubation of the isolates under different levels of media concentration, temperature, pH, light intensity and aeration. Both the species showed optimum growth in terms of total chlorophyll at a temperature of 25oC. However, significant differences (at 5% level) in growth were observed for the isolates under other conditions. The optimum growth of Chlamydomonas noctigama was observed for the vitamin B1+B6, whereas there was no significant difference on growth of Nostoc spongiaeforme for any vitamin supplement. The optimum pH for the growth of Chlamydomonas noctigama and Nostoc spongiaeforme were 6.5 and 7.5, light intensity 110 µEm-2s-1and 70 µEm-2s-1, and media concentration 2x and 1x of normal concentration, respectively. Bangladesh J. Sci. Ind. Res.51(3), 183-192, 2016